Cognitive rehabilitation in paediatric acquired brain injury—A 2-year follow-up of a randomised controlled trial - Sargénius, Hanna L.; Andersson, Stein; Haugen, Ingvild; Hypher, Ruth; Brandt, Anne Elisabeth; Finnanger, Torun G.; Rø, Torstein B.; Risnes, Kari; Stubberud, Jan (Frontiers in Neurology, 2023)
Background Goal management training (GMT), a metacognitive rehabilitation method that has been demonstrated to improve executive function (EF) in adults with acquired brain injury (ABI), could potentially be effective for children in the chronic phase of ABI. In a previously published randomised controlled trial (RCT), the efficacy of a paediatric adaptation of GMT (pGMT) compared to a psychoeducative control intervention (paediatric Brain Health Workshop, pBHW) was investigated. Comparable improvements in EF in both groups were found at 6-month follow-up. However, a specific effect of pGMT could not be conclusively proven. The present study reports 2-year follow-up data (T4; T1: baseline, T2: post-intervention, T3: 6-month follow-up, and T4: 2-year follow-up) from this original RCT. Methods A total of 38 children and adolescents and also their parents completed questionnaires tapping into daily life EF. Explorative analyses were conducted comparing the 2-year follow-up data (T4) with the baseline (T1) and 6-month follow-up data (T3) for T4-participants in the two intervention groups (pGMT; n = 21, pBHW; n = 17), and we also assessed T4-participants vs. non-responders (n = 38) in the RCT. Primary outcome measures were the Behavioural Regulation Index (BRI) and the Metacognition Index (MI) derived from the Behaviour Rating Inventory of Executive Function (BRIEF) parent report. Results No difference between intervention groups was found (BRI, F = 2.25, p = 0.143, MI, F = 1.6, p = 0.213), and no time*group interaction (BRI, F = 0.07, p = 0.976, MI, F = 0.137, p = 0.937) could be seen at the 2-year follow-up. Nevertheless, both pGMT and the pBHW groups improved daily EF as measured by parental reports over time from the baseline to T4 (p = 0.034). T4 participants and non-responders shared similar baseline characteristics. Conclusion Our results extend the findings from the 6-month follow-up previously published. Both pGMT and pBHW groups sustained their improvements in daily life EFs from the baseline, but additional effectiveness of pGMT relative to pBHW was not found.